Analisis Efisiensi Penggunaan Faktor Produksi pada Usahatani Padi Sawah di Kecamatan Gambut Kabupaten Banjar - Noor Fauziah; Abdurrahman Abdurrahman; Yusuf Azis (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Kecamatan Gambut, where the largest rice cultivation area is located, is one of important rice producers in Kabupaten Banjar. The study analyzes the effect of production factor use on the rice harvest, and analyzes the status of technical and economic elliciency of procluclion factors use on rice farming. The result shows that the value of technical efficiency (TCR) is 0.972 (97.2%), which mean that in general the resource use approachestechnica/. efficient (scale 0- 1 ). The allocative efficiency test finds that land achievesprice efficiency, while the use of capital and labor is not efficient. It is suspected due' to the excess use of capital and labor.